THE ORGANOLEPTIK TEST EFFERVESCENT POWDER PULAI LEAVES (Alstonia scholaris (L.) R.BR. - Dian Wulansari; Silvi Leila Rahmi; Fauziah Fiardilla; S. Ningsih (Jurnal Pengembangan Agroindustri Terapan, 2023)
This study aims to determine the effect of the comparison of citric acid-tartaric acid on the characteristics of effervescent powder of pulai leaves (alstonia scholaris). This research was conducted using a completely randomized design (crd). Each treatment was repeated 4 times to obtain 20 units of trial. The ratio of citric acid-tartaric acid significantly affected organoleptic properties of effervescent effect, sparkle effect, and overall acceptance. The results showed that the comparison of citric acid-tartaric acid 1:2 treatment yielded the best treatment with effervescent effect 4.56 (gas formed), sparkle 3,84 (somewhat soda effect), color 3.20 (somewhat like), overall acceptance of 3.12 (somewhat like), and plural comparisons of 4.08 (as good as the R)